Effects of remote learning during COVID-19 lockdown on children's learning abilities and school performance (2023)
This systematic review describes the effects of COVID-19 lockdowns on children’s learning and school performance. A systematic search was conducted using three databases. A total of 1787 articles were found, and 24 articles were included. Overall, academic performance was negatively affected by COVID-19 lockdowns, with lower scores in standardized tests in the main domains compared to previous years. Academic, motivational, and socio-emotional factors contributed to lower performance. Educators, parents, and students reported disorganization, increased academic demands, and motivational and behavioral changes. Teachers and policymakers should consider these results in developing future education strategies.